ORGANIZATIONAL CULTURE AS THE DOMINANT DRIVER OF EMPLOYEE PERFORMANCE: THE ROLE OF LEADERSHIP STYLE AND THE PARADOX OF WORK MOTIVATION IN INDONESIAN PORT AUTHORITY - Eko Subekti Arrohman; Sri Rahayu; Rifda Fitrianty (STMIK Indonesia Banda Aceh, 2026)
This study investigates the simultaneous influence of work motivation, leadership style, and organizational culture on employee performance within a public sector maritime institution undergoing structural transformation, specifically at Kantor Kesyahbandaran dan Otoritas Pelabuhan Class III Tanjung Pakis following its elevation from a port administration unit to a full port authority. Using a quantitative explanatory approach, data were collected from all active employees through a structured questionnaire measuring four latent variables with twenty-four indicators on a five-point Likert scale, and Partial Least Squares Structural Equation Modeling was employed to test the hypothesized relationships. The findings reveal a distinct hierarchy among the examined determinants, with organizational culture emerging as the dominant driver of employee performance, leadership style retaining meaningful yet secondary influence, and work motivation demonstrating no significant direct effect, thereby challenging the universal applicability of classical motivation theories in bureaucratic maritime contexts and underscoring the primacy of collective value systems in shaping employee conduct. These results carry important implications for human resource development in public maritime agencies, suggesting that cultural intervention strategies should receive primary emphasis with leadership development oriented toward cultural stewardship rather than isolated behavioral training, while also contributing to organizational behavior scholarship by demonstrating the need for contextual calibration of established theoretical frameworks and identifying a motivation paradox that warrants further investigation through mediating mechanisms and longitudinal designs.